Fully Automated 68Ga-Labeling and Purification of Macroaggregated Albumin Particles for Lung Perfusion PET Imaging - Blanc-Béguin, Frédérique; Masset, Julien; Robin, Philippe; Tripier, Raphaël; Hennebicq, Simon; Guilloux, Valérie; Vriamont, Charles; Warnier, Corentin; Cogulet, Virginie; Eu, Peter; Salaün, Pierre-Yves; Le Roux, Pierre-Yves (Frontiers in Nuclear Medicine, 2021)
Lung PET/CT is a promising imaging modality for regional lung function assessment. Our aim was to develop and validate a fast, simple and fully automated GMP compliant [68Ga]Ga-MAA labelling procedure, using a commercially available [99mTc]Tc-MAA kit, a direct gallium-68 eluate and including a purification of the [68Ga]Ga-MAA. Method: The synthesis parameters (pH, heating temperature) were manually determined. Automated 68Ga-labelling of MAA was then developed on a miniAIO (Trasis®, Ans, Belgium) module. An innovative automated process was developed for the purification. The process was then optimized and adapted to automate both the [68Ga]Ga-MAA synthesis and the isolation of gallium-68 eluate required for the pulmonary ventilation PET/CT. Results: The 15 minutes process demonstrated high reliability and reproducibility, with high synthesis yield (> 95 %). Mean [68Ga]Ga-MAA radiochemical purity was 99 % ± 0.6 %. The 68Ga-labelled MAA particles size and morphology remained unchanged. Conclusion: A fast, user friendly and fully automated process to produce GMP [68Ga]Ga-MAA for clinical use was developed. This automated process combining the advantages of using a non-modified MAA commercial kit, a gallium-68 eluate without pre-purification and an efficient final purification of the [68Ga]Ga-MAA may facilitate the implementation of lung PET/CT imaging in nuclear medicine departments.